Chinese Consumers’ Herd Consumption Behavior Related to Korean Luxury Cosmetics: The Mediating Role of Fear of Missing Out - Kang, Inwon; He, Xue; Shin, Matthew Minsuk (Frontiers in Psychology, 2020)
Chinese consumers’ lavish and collective spending on Korean luxury cosmetics brands is well documented. This study examines why this consumption behavior occurs, hypothesizing that it is driven by a “fear of missing out” (FoMO). In other words, in order to derive psychological comfort, consumers with high FoMO may be prone to developing high brand involvement, leading to their collective consumption of certain luxury brands. In consumer studies, such collective consumption behavior is referred to as herd behavior. Thus, the main research question of this study is, “why do Chinese consumers show herd consumption behavior toward certain luxury brands?” We propose that consumers who are attracted to luxury brands and possess high FoMO will develop higher brand involvement, leading to herd consumption behavior toward such brands. To validate this proposition, this study surveyed Chinese consumers. The collected data were analyzed using the structural equation modeling (SEM) method, conducted within SPSS and AMOS. The results provide theoretical explanations as to why Chinese consumers indulge in collective obsession-like stockpiling consumption toward certain luxury brands, as well as several managerial implications related to this behavior.